DAMPAK GAME ONLINE TERHADAP SPIRITUALITAS REMAJA KRISTEN DI KOTA MANADO - Jendry Kewas; Benny. B. Binilang; Samuel Selanno (Manna Rafflesia, 2025)
Technological developments from the Society 1.0 era to Society 5.0 have drastically changed human lifestyles, including in Indonesia, which is still in the process of adapting to the Fourth Industrial Revolution. These advancements, through digital devices such as smartphones, have made access to information and entertainment easier, but have also given rise to new phenomena such as online gaming addiction, which erodes human values. Various cases at the global, national, and local levels highlight the negative impacts of online gaming, ranging from violent behaviour to moral decay among children and adolescents in the city of Manado. This study aims to analyse the effects of online gaming addiction on the behaviour and spiritual values of students in the digital age. Using descriptive qualitative methods and interviews, it can be concluded that online gaming addiction has a significant impact on various aspects of students' lives, including physical, mental, and social health, as well as academic achievement. In an educational context, this addiction also affects affective assessment, particularly spiritual attitudes, which are closely related to the formation of moral character and spiritual life. Excessive online gaming has the potential to undermine moral values, disrupt social relationships, and weaken students' spiritual commitment. Therefore, supervision from educators and parents is crucial to ensure students can manage their online gaming use wisely, thereby maintaining.